Pengalaman Mahasiswa Rantau tentang Adaptasi Lintas Budaya di Salatiga: Suatu Tinjauan Teologi Interkultural - Otniel Aurelius Nole (Program Pascasarjana UKIM, 2023)
Salatiga is a city known for its diverse cultures, so there are not only Javanese cultures but also cultures that come from outside Java. The arrival of students who migrate to study and have particular cultural origins has an impact on this as well. Cultural diversity motivates students to make cross-cultural adaptations. From this, students certainly have life experiences related to life and the social world. This research aims to investigate the experiences of overseas students about cross-cultural adaptation in Salatiga with a review of intercultural theology. The researcher used a qualitative method with a case study design. The data analysis approach used was an interpretative phenomenological analysis. The participants were three theology students from different cultures and were selected based on a purposive sampling technique. The researcher found that the three participants had unique and distinctive life experiences about adapting across cultures. For them, there were challenges at first, but the atmosphere shifted to feelings of excitement and learning opportunities from experiencing other cultures. In the end, the presence of diverse cultures certainly makes them realize the goodness of God, who has created cultural diversity.